The Lost World - "Arthur Conan Doyle" (Puffin books London, 2019)
The story follows Professor Challenger, an eccentric and controversial scientist, who claims to have discovered a plateau in the Amazon rainforest where prehistoric creatures still exist. Skeptical of his claims, a group of individuals set out on an expedition to verify his story.